Decomposition and nitrogen mineralization from green manures intercropped with coffee tree - Cardoso, Rosileyde Golçalves Siqueira; Pedrosa, Adriene Woods; Rodrigues, Mateus Cupertino; Santos, Ricardo Henrique Silva; Cecon, Paulo Roberto; Martinez, Herminia Emilia Prieto (Coffee Science - ISSN 1984-3909, 2018)
The knowledge about the rate of decomposition and nitrogen mineralization of green manures provides synchronization with the higher absorption stage by the coffee tree. The rate of decomposition and nitrogen mineralization varies according to the species of green manure and with the environmental factors. The aim of the present study was to evaluate the decomposition and nitrogen mineralization of two green manures intercropped with coffee trees for three different periods. The experiment was divided into two designs for statistical analysis, one referring to the characterization of plant material (fresh mass, dry matter, dry matter content, nitrogen concentration and accumulation in the jack bean (Canavalia ensiformis) and hyacinth bean (Dolichos lablab) and another to evaluate the rate of decomposition and N mineralization of these species. The decomposition rate decreased in both species as their growth time increased in the field. The decomposition was influenced by the phenology of green manures. Nitrogen mineralization of the jack bean decreased as the growth period in the field increased and was faster than hyacinth bean only when cut at 60 days. The N mineralization was slower than mass decomposition in both species.